2013
DOI: 10.1016/j.jaci.2012.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death ligand 2 regulates TH9 differentiation and induction of chronic airway hyperreactivity

Abstract: Background Asthma is defined as a chronic inflammatory disease of the airways; however, the underlying physiologic and immunologic processes are not fully understood. Objective The aim of this study was to determine whether TH9 cells develop in vivo in a model of chronic airway hyperreactivity (AHR) and what factors control this development. Method We have developed a novel chronic allergen exposure model using the clinically relevant antigen Aspergillus fumigatus to determine the time kinetics of TH9 deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 66 publications
(97 reference statements)
0
70
0
Order By: Relevance
“…This highlights the need for well-defined asthma models specifically suited for addressing disease mechanisms or for evaluating existing and novel therapies. Chronic sensitisation protocols have been reported to result in models of pronounced Th2-type disease [10,11,12,15], more mixed types of diseases [14,30,31], and even dexamethasone insensitive disease [32]. Our cat allergen-induced asthma model exhibits characteristics of Th17/neutrophilic asthma with increased neutrophil numbers in BAL and increased levels of IL-17a in lung tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This highlights the need for well-defined asthma models specifically suited for addressing disease mechanisms or for evaluating existing and novel therapies. Chronic sensitisation protocols have been reported to result in models of pronounced Th2-type disease [10,11,12,15], more mixed types of diseases [14,30,31], and even dexamethasone insensitive disease [32]. Our cat allergen-induced asthma model exhibits characteristics of Th17/neutrophilic asthma with increased neutrophil numbers in BAL and increased levels of IL-17a in lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, both improved chronic OVA protocols [10] and protocols with relevant inhaled allergens (e.g. dust mite, pollen and moulds [11,12,13,14]) have been developed. Chronic asthma models have been employed in a number of studies of disease and treatment mechanisms [12,14,15,16,17,18], but there is still a need for improved models of allergy and asthma induced by allergens relevant for human disease.…”
Section: Introductionmentioning
confidence: 99%
“…Th9 cells play a pivotal role in health and disease. Th9 cells have been shown to exacerbate the airway allergic immune response by recruiting eosinophils and mast cells to the lungs, increasing mucus production, and production of serum IgE (11,12). Th9 cells further contribute to the host-immune reaction against helminth infections and tumors (7,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Cd4mentioning
confidence: 99%
“…A recent study by Kerzerho and colleagues indicated that programmed cell death ligand 2 (PD-L2) downregulates the differentiation of Th9 cells in an Aspergillus fumigatus-induced model of chronic airway hyper-responsiveness (AHR). Blocking PD-L2 results in an increase of IL-9 production albeit no effect on IL-4 produced by Th2 cells [32].…”
Section: Co-stimulatory Factorsmentioning
confidence: 98%
“…Exposure of mice to house dust mite results in the rapid accumulation Th9 cells that produce IL-9 in the absence of IL-13, IL-10 and IFN-γ, which directly correlated with the severity of AHR and anti-IL-9 treatment decreased airway inflammation [26]. A recent study of chronic AHR induced by intranasal Aspergillus fumigatus lysates reveals that Th9 cells did not coexpress IL-4, IL-10, and IL-13 [32] …”
Section: Asthmaand Airway Hyper-responsiveness (Ahr)mentioning
confidence: 99%